Synthesis of p-Aminophenol from p-Nitrophenol Using CuO-Nanoleaf/g-Al2O3 Catalyst - Didik Sudarsono; Eriawan Rismana; Slamet Slamet (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The CuO-nanoleaf/g-Al2O3 catalyst was synthesized through wet chemical impregnation and had promising catalytic activity in reducing p-Nitrophenol (PNP) into p-Aminophenol (PAP). The synthesis was conducted in situ with Ethylene Glycol as a stabilizer agent of the CuO-nanoleaf structure and g-Al2O3 as catalyst support with high adsorption ability. Furthermore, the crystal phase, morphology, element composition, and specific surface area were investigated by X-Ray Diﬀraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and N2 adsorption-desorption, respectively. The XRD pattern showed the crystal phase of CuO and g-Al2O3 in the composite, and the morphology was successfully reported using FESEM. The increase in the specific surface area of the catalyst indicates that the CuO material was well composited in g-Al2O3. The catalyst has good activity in reducing PNP to PAP with 93.53% PNP conversion within 4 min. In addition, the reduction reaction of PNP with excess NaBH4 could be categorized as pseudo-first order kinetic with a constant rate of 0.6935 min−1 for CuO-nanoleaf/g-Al2O3 catalyst. The loading catalyst and temperature reaction effect on PNP conversion were also investigated. The results showed that 94.18% PNP conversion was obtained within only 2.5 min under the optimized conditions. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).